An 'omics' approach towards the characterisation of laboratory scale anaerobic digesters treating municipal sewage sludge. (1st January 2016) - Beale, D.J.; Karpe, A.V.; McLeod, J.D.; Gondalia, S.V.; Muster, T.H.; Othman, M.Z.; Palombo, E.A.; Joshi, D.
Abstract: In this study, laboratory scale digesters were operated to simulate potential shocks to the Anaerobic Digestion (AD) process at a 350 ML/day wastewater treatment plant. The shocks included high (42 °C) and low (32 °C) temperature (either side of mesophilic 37 °C) and a 20% loading of fats, oil and grease (FOG; 20% w:v). These variables were explored at two sludge retention times (12 and 20 days) and two organic loading rates (2.0 and 2.5 kgTS/m 3 day OLR). Metagenomic and metabolomic approaches were then used to characterise the impact of operational shocks in regard to temperature and FOG addition, as determined through monitoring of biogas production, the microbial profile and their metabolism. Results showed that AD performance was not greatly affected by temperature shocks, with the biggest impact being a reduction in biogas production at 42 °C that persisted for 32 ± 1 days. The average biogas production across all digesters at the completion of the experiment was 264.1 ± 76.5 mL/day, with FOG addition observed to significantly promote biogas production (+87.8 mL/day). Metagenomic and metabolomic analyses of the digesters indicated that methanogens and methane oxidising bacteria (MOB) were low in relative abundance, and that the ratio of oxidising bacteria (methane, sulphide and sulphate) with respect to sulphate reducing bacteria (SRB) had a noticeable influence on biogas production. Furthermore, increased biogas production correlated with an increase in short chain fatty acids, a product of the addition of 20% FOG. This work demonstrates the application of metagenomics and metabolomics to characterise the microbiota and their metabolism in AD digesters, providing insight to the resilience of crucial microbial populations when exposed to operational shocks. Graphical abstract: Highlights: Metagenomics and metabolomics provide insight into anaerobic digester operation. Methanogen and methane oxidising bacteria were found in relative low numbers. Metabolomics highlighted increased biogas in digesters with increased SCFAs. Biogas related biota were varied while biogas production was fairly constant.